New Nordic architecture: Sustaining food, nature, and architecture based on local resources and the new Nordic kitchen manifesto - Oxelman, Maria (My University, 2022)
There are many connections between architecture and food - they are creative practices highly connected to history, trends, culture, and constants in our lives. Today, our globalized world has made us disconnected to the natural processes in both fields, as products are highly processed through several steps before it is reached its final destination. The New Nordic Kitchen is a movement within food that promotes use of food and traditions from the Nordic region in an environmentally sound and healthy way. A manifesto was formulated in 2004 to guide chefs in their work. In this thesis, the manifesto is translated to architecture and used as the concept. Consequetly, the thesis engages in theories in architecture: Regenerative design, wellbeing and comfort, and primitivism. Furthermore, the thesis discusses the standardized construction industry in opposition to handcraft and local production. Vernacular Nordic architecture is an important reference, and natural, local materials are used. The site of the thesis is Gerlesborg in Bohuslän, Sweden. Because of the connection to food, the program of the project is a restaurant where all food can be gathered in the immediate surroundings, New Nordic Kitchen, regenerative design, local materials, vernacular architecture. Keywordsjust like the materials of the building. Many artists live in Gerlesborg, and therefore, an additional building for exhibitions and to gather in is placed on the site. On the grass field where the buildings stand, three buildings completely clad in straw rise. The fourth is a greenhouse, prolonging the vegetable season for the restaurant. Views towards a mountain and the sea are important to the building complex, and people are invited to experience them with the building. The manifesto showed to be easily applicable to regenerative architecture. It is a clear strategy, and one can interpret and put different amount of importance to different points. If to be built in reality, a close collaboration with craftsmen would be important, as the project works outside of regular building regulations.
Keywords: New Nordic Kitchen, regenerative design, local materials, vernacular architecture